Using normative inquiry and co-design to embed inclusive design in social design education. (4th March 2023) - Cifter, Abdusselam Selami; Dong, Hua; Cook, Sharon; Ayna, Aylin
Abstract: Collaborations of universities with different stakeholders can extend students' learning and result in capacity development among all the collaborators. The project described in this article, SIDe, involved partners from the UK and Turkey who develop a mechanism together to effectively embed inclusive design and co-design in social design education. The knowledge production through normative inquiry and the experience of a shared equal voice among all the partners resulted in the SIDe Model, enabling collaborators to understand their unique contributions. The model was tested with students from four different disciplines at the Faculty of Architecture, Mimar Sinan Fine Arts University. This article offers original insights into how normative inquiry can be realized in course design and project execution to drive inclusion in social design education; it also provides the improved design process model – the SIDe model – to facilitate potential wider adoption of the good practice.